2019
DOI: 10.46778/goputeb.521213
|View full text |Cite
|
Sign up to set email alerts
|

Sağlik Hi̇zmetleri̇ Meslek Yüksekokulu Öğrenci̇leri̇ni̇n Yazma Kaygilari Ve Öz-Yeterli̇k Algilarinin Çeşi̇tli̇ Deği̇şkenler Açisindan İncelenmesi̇

Abstract: Bu çalışmada; Sağlık Hizmetleri Meslek Yüksekokulu (SHMYO) öğrencilerinin yazma kaygıları ve öz-yeterliklerinin cinsiyet, sınıf, öğretim türü, gelir düzeyi, ikamet yeri, mezun olunan lise türü ve eğitim alınan branş değişkenleri açısından anlamlı farklılık gösterip göstermediğinin belirlenmesi amaçlanmaktadır. Araştırmada betimsel tarama modeli kullanılmıştır. Araştırmanın örneklem grubunu 2018-2019 eğitim-öğretim yılı bahar döneminde Sivas Cumhuriyet Üniversitesi SHMYO’da eğitim görmekte olan 340 kız, 115 erk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
1
0
7
Order By: Relevance
“…In a meta-analysis evaluating 50 different factors effecting students' academic performance, self-efficacy and self-confidence were concluded as the strongest parameters (Richardson, Abraham & Bond, 2012). In this research, SGSES total scores are similar or higher than some conducted studies (Arslan, 2019;Arslan, Ilıman & Aslan, 2019;Gün, Aslantekin & Karadağ, 2021;Sarani et al, 2020). The SGSES was administered to the participants twice as; before and after the…”
Section: Discussionsupporting
confidence: 54%
“…In a meta-analysis evaluating 50 different factors effecting students' academic performance, self-efficacy and self-confidence were concluded as the strongest parameters (Richardson, Abraham & Bond, 2012). In this research, SGSES total scores are similar or higher than some conducted studies (Arslan, 2019;Arslan, Ilıman & Aslan, 2019;Gün, Aslantekin & Karadağ, 2021;Sarani et al, 2020). The SGSES was administered to the participants twice as; before and after the…”
Section: Discussionsupporting
confidence: 54%
“…Because it has been found that people with high self-efficacy are more combative and make more effort to cope with problems (Asarli, 2012). In other studies (Arslan, 2019;Satıcı, 2014;Tokyürekli, 2020), similarly, it has been found that individuals who do not trust their own abilities make little effort when they encounter problems and therefore their belief that they will fail is strengthened, thus their belief in achieving what they are aiming for is weakened. Indeed, in the literature that indicate that there is a positive relationship between teacher efficacy studies with professional success (Lu, Siu & Cooper, 2005) supports this argument.…”
Section: Introductionmentioning
confidence: 84%
“…Barnes'e (2004) (Asarlı, 2012). Diğer taraftan bireyler hedeflerine ulaşmak için yeterli düzeyde bilgi ve beceriye sahip olsalar dahi eğer öz-yeterlik algıları düşük ise kendilerine yönelik olumsuz algıları nedeniyle yaptıkları işten çabuk vazgeçerek başarısız olurlar (Arslan, 2019;Satıcı, 2014;Yıldırım & İlhan, 2010). Yapılan başka çalışmalarda (Satıcı, 2014;Tokyürekli, 2020)…”
Section: Introductionunclassified
“…Dayanıklılık (1) Öğretmenlik 59 147,35 4,543 3 ,208 (2) Antrenörlük 84 125,95 (3) Yöneticilik 80 132,55 (4) Rekreasyon 39 117,32…”
Section: Veri Toplama Araçlarıunclassified